Analysis of Syntatic Language Error Level in Students' Persuasive Speech Essay Texts of Grade IX SMIP Al Mubtadi-Ien Bantul District - Riswanda Himawan (Universitas Muhammadiyah Prof. DR. HAMKA, 2020)
Text-based language learning in the 2013 curriculum requires students to be active so that at the end of learning students are expected to be able to produce an output product from the material that has been taught. In producing these outputs, it is necessary to have an in-depth understanding of the material related to the selection and arrangement of appropriate vocabulary. In line with this statement. This study aims to determine the language errors at the syntactic level in the results of presuasive speech text essays of grade IX students of SMP Islam Prestasi Al-Mubtadi-Ien Bantul Regency. This research uses a qualitative approach that is descriptive. The data source used in this study was a text essay of persuasive speech for grade IX students of SMPIP Al-Mubtadi-Ien Bantul. The data analysis method used in this study was the equivalent method with the analysis technique in the form of a reference. The references used to analyze the data in this study are the Big Indonesian Dictionary (KBBI), the Acronym for General Guidelines for Indonesian Spelling (PEUBI), and the opinions of experts who are relevant to this research. Of the 12 articles analyzed, there were 3 ambiguous sentences, 5 with non-standard sentences, 5 with unclear sentence errors, 8 essays with sentences that experienced redundant words, and 6 sentences with inappropriate diction. As well as 4 clauses with unclear sentence logic. The results of the study concluded that language errors at the syntactic level in the students' essays were caused by the lack of student references in understanding language material. As well as the habits of students in choosing and applying phrases, clauses and sentences when compiling essays.